Genetic Profiling of Sida rhombifolia Originated from Several Indonesian Ethnicities Based on Sequence-Related Amplified Polymorphism Markers - Jumailatus Solihah; Isma Kurniatanty; Dyah Subositi; Anshary Maruzy; Ika Nugraheny Ari Martiwi; Erny Qurrotul Ainy; Khoirul Anam; Aslikh Lana Dina (Jurnal Biodjati, 2021)
Sida rhombifolia is one of wild flowering plants that grows easily in many habitats with moderate humidity, with some usefulness in traditional medicine. Genetic characterization of Sida rhombifolia accessions originated from 12 ethnicities of Indonesia was analyzed based on Sequence-Related Amplified Polymorphism (SRAP) Markers. The genomic DNA were extracted from leaf samples and then were characterized by using the SRAP marker system according to Li and Quiros (2001). Nine pairs of SRAP primer resulted high polymorphic bands and were used in the genetic profiling. The data analysis was performed using GenAlEx to calculate genetic distance, Principal coordinate analysis, and Analysis of Molecular Variance (AMOVA), also using POPGENE to assess genetic diversity (Hs and Ht) and Nm to predict gene flow among populations. The coordinate analysis showed that the accessions originated from ethnicities along Wallacean line tend to differ genetically from most other locations. However, the results of analysis of molecular variance suggested that there were only slight differences (0.1%) found between ethnicities, while most genetic variances (99.9%) were found mostly among accessions within populations. The results suggested that there was an extensive genetic flow and plant spreading among Sida rhombifolia plant populations, resulting more homogenous genetic characters among most populations, while high diversity within population. The calculation of the number of migration (Nm = 1.7341) confirmed that the high rate of gene flow had occurred between populations.